A Wegner Estimate for Multi-Particle Random Hamiltonians - Kirsch, Werner (Журнал математичної фізики, аналізу, геометрії, 2008)
We prove a Wegner estimate for a large class of multi-particle Anderson Hamiltonians on the lattice. These estimates will allow us to prove Anderson localization for such systems. A detailed proof of localization will be given in a subsequent paper. Mathematics Subject Classification: 82B44, 35R60, 35P20.